P7 Relationship between function, quality of life and balance in persons with chronic ankle instability. (17th September 2017) - Brazer, O; Solomon, S; Manning, S; Groulx, D; Fadool, M; Wikstrom, EA; Freund, J; Vallabhajosula, S
Abstract : Study Design: Cross-sectional. Objectives: To investigate the relationship between subjective measures of function and quality of life, and objective measures of balance in individuals with Chronic Ankle Instability (CAI). Background: CAI results due to an inadequately healed ankle sprain, and may impact the individual's balance and quality of life. However, it is unknown how they are related. Methods and Measures: Participants: 1) CAI group (n=18; age 22.4±2.8 years) had a history of at least 1 significant ankle sprain with feelings of instability and/or recurrent sprain, 2) Copers (n=15; age 22.4±3.2 years) also sustained 1 significant ankle sprain, but are able to return to their pre-injury levels without residual symptoms and 3) Control (n=18; 22.2±3.0 years), who never had ankle injury. Static balance was tested using single leg standing on the Biodex Balance System platform set to levels of varying stability. Dynamic balance was tested using Y-balance system. Foot and Ankle Ability Measure (FAAM) and the Foot and Ankle Outcome Score (FAOS) surveys were administered. Results: For CAI group, the FAOS quality of life subscale was negatively correlated with sway index and area when the platform was stable (both r>=−0.52; p<0.026). Also the FAOS activities of daily living and pain subscales negatively correlated with maximum reach in the posteromedial direction of the Y-balance test (both r>=−0.49; p<0.037). For Copers, the FAOS symptoms subscale negatively correlated with sway index when the platform was stable (r=−0.54; p=0.037). For Controls the FAOS symptoms subscale showed negative moderate significant correlation with sway index and area on the very unstable platform level. Conclusions: For those with a history of ankle sprain, subjective measures seemed to be related to performance on the least challenging static balance and dynamic balance test. Subjective measures of quality of life and function do not seem to be related to more challenging static balance tests.